SPLIT QUATERNION MATRICES - Alagoz, Yasemin; Oral, Kursat Hakan; Yuce, Salim (UNIV MISKOLC INST MATH, 2012)
In this paper, we consider split quaternions and split quaternion matrices. Firstly, we give some properties of split quaternions. After that we investigate split quaternion matrices using properties of complex matrices. Then we define the complex adjoint matrix of split quaternion matrices and we describe some of their properties. Furthermore, we give the definition of q-determinant of split quaternion matrices.
Keywords: quaternions; split quaternions; matrices of split quaternions; Mathematics